Strategy and political geography of the armed conflict in valle del cauca (2010)
Hereby we present an explanation of the causes that have determined geopolitical changes derived from the armed confrontation between the state force and paraestatal groupings in Valle del Cauca (Colombia). This paper is the first part of a project encompassing three central components of the armed conflict and its regional impact: (a) the relevance of geography to understand political and economic transformations arising from local war; (b) the economic and financial structure supporting the formation and survival of irregular armies within a determined geographic region; (c) the strategic correlations that differentiate and assimilate the groups fighting for predominance in the regional geography. We restricted the research to the first of the three components. A later work should show us the correlations between paraestatal associations, their new identities and geopolitical impact within the whole Colombian geography.